Ensino da astronomia no Brasil: educação formal, informal, não formal e divulgação científica - Langhi, Rodolfo [UNESP]; Nardi, Roberto [UNESP] (My University, 2009)
This paper is part of a broader research on astronomy education and teachers' education, presenting a national overview about this subject. It tries to set up a classification system for Brazilian astronomy institutions and other enterprises, taking into consideration their aims, such as formal, informal, non-formal education, as well those addressed to the popularization of this science. We comment, in a brief essay, the importance of the contextual performance of these instances for the astronomy education, raising a challenge to be considered, related to the study of possible relations among these institutions and enterprises, aiming the advancement of the astronomy education, in a motion against the local and punctual activities dispersion and pulverization. We argue that the research in astronomy education has potential to exert this joint role. © by the Sociedade Brasileira de Fsíca.
Astronomy education in Brazil: Formal, informal, non-formal education, scientific popularization
Keywords: Astronomy Clubs; Astronomy Education; Astronomy Institutions; Astronomy Popularization; Enterprises; Formal; Informal Education; Non Formal; Observatories; Planetariums